Strategi pemasaran kerupuk ikan teri di Desa Terapung Kecamatan Mawasangka Kabupaten Buton Tengah - Alfikram, La Ode; Yusuf, Sarini; Piliana, Wa Ode; Siang, Roslindah Daeng; Lawelle, Sjamsu Alam (Universitas Halu Oleo, 2023)
This study aims to determine the marketing strategy for the Cahaya Faiz anchovy cracker business in Floating Village, Mawasangka District, Central Buton Regency in August 2022. Data was obtained through observation, interviews and documentation. The data analysis used was SWOT analysis, by using a Likert scale. The results of the analysis show that the S-O Strategy utilizes location inputs to produce anchovy cracker ingredients, provides satisfaction with the quality of the anchovy crackers purchased, a fairly good partnership relationship between business actors and fishermen. The W-O strategy maximizes product promotion so that it is better known by the wider community both directly and online and improves marketing and workforce management strategies. The S-T strategy gives the public confidence in processed anchovy cracker products, improves the quality of anchovy cracker products and increases the number of processed anchovy cracker products. The W-T strategy maximizes the availability of raw materials during the anchovy low season.